Efeitos da maturação biológica sobre o custo energético, potência aeróbia, máximo déficit acumulado de oxigênio e performances de nadadores - Silva, Maria de Souza [UNESP] (2013)
The aim of the study was to investigate the effects of biological maturation on energy cost (EC), maximal aerobic power (VO2PEAK), maximal accumulated oxygen deficit (MAODRED) and performances of swimmers belonging to categories petiz, childish, juvenile, junior and senior which were classified into groups after determining the biological age (Tanner, 1962).Two groups of swimmers from state and national levels (9 in study 1 and 34 in study 2) in study 1 swimmers were evaluated, performed two maximum effort 400m front crawl, the technique of back extrapolation was used to measure the peak oxygen consumption (VO2PEAK) for two gas analyzers: Quark (PFT, Cosmed, Rome Italy) and VO2000 (Aerosport, Medgraphics). The anaerobic energy contribution alactic (CeALA) and lactic (CeLAT), (MAODRED) were also determined. The CeLAT and P400, and no significant differences were correlated between the two gas analyzers, the CeALA significant difference. It is concluded that comparisons of data from these two gas analyzers should be performed with caution. The 34 swimmers Study 2 performed a maximal effort 400m front crawl to determine the EC, CeALA, CeLAT, VO2PEAK, MAODRED, through the technique of back extrapolation. Oxygen consumption was measured by gas analyzer Quark (PFT, Cosmed, Rome Italy) (Day 1). In subsequent days maximum efforts of 100 and 200 were performed and it was determined the stroke length (SL), stroke rate (SR) and stroke index (SI). The time was recorded every 25m for all distances. Body composition determined by dual energy x-ray absorptiometry (DEXA). The groups were classified according to the biological maturation: four athletes in stage 2 (P2), six at stage three (P3), 13 in stage 4 (P4) and the nine stage 5 (P5). The CeLAT, MAODRED, the EC, the [Lac]PEAK and VO2PEAK were higher in the more mature groups when compared to less mature. The CeALA CeAER and showed no significant differences between groups. In 400m, SI was higher in the...